Ratio of ellipticities between 192 and 208 nm (R1): An effective electronic circular dichroism parameter for characterization of the helical components of proteins and peptides. Issue 11 (7th August 2017) - Banerjee, Raja; Sheet, Tridip
Abstract: Circular dichroism (CD) spectroscopy represents an important tool for characterization of the peptide and protein secondary structures that mainly arise from the conformational disposition of the peptide backbone in solution. In 1991 Manning and Woody proposed that, in addition to the signal intensity, the ratio between [ θ ] n π * and [ θ ] π π * ǁ (( R2 ) ≅ [θ]222 /[θ]208 ), along with [ θ ] π π * ⊥ and [ θ ] π π * ǁ (( R1 ) ≅ [θ]192 /[θ]208 ), may be utilized towards identifying the peptide/protein conformation (especially 310 ‐ and α‐helices). However, till date the use of the ratiometric ellipticity component for helical structure analysis of peptides and proteins has not been reported. We studied a series of temperature dependent CD spectra of a thermally stable, model helical peptide and its related analogs in water as a function of added 2, 2, 2‐trifluoroethanol (TFE) in order to explore their landscape of helicity. For the first time, we have experimentally shown here that the R1 parameter can characterize better the individual helices, while the other parameter R2 and the signal intensity do not always converge. We emphasize the use of the R1 ratio of ellipticities for helical characterization because of the common origin of these two bands (exciton splitting of the amide π→ π* transition in a helical polypeptide). This approach may become worthwhile and timely with the increasing accessibility of CD synchrotron sources.